Health care reform and globalisation : the US, China and Europe in comparative perspective - Watson, Margaret, 1948- (Abingdon, Oxon : Routledge, 2013)
"In the post-Cold War, post financial crisis era, health care is an issue of critical political, personal and economic concern. In the US, plans to address a troubled health care model were met by vocal opposition. In the UK and post-communist Europe, attempts to introduce aspects of that model have resulted in controversy and violent protests, while China and Russia have recently backpedalled on marketising reforms. This innovative book provides a timely analysis addressing the many dimensions of radical health care change. Bringing together three major geopolitical regions with strikingly different recent histories, this international cast of contributors, examines reform in US, China and Europe within a single study frame. They look at the processes that have been involved when countries with such diverse starting points try to move towards a globally shared health care framework. An underlying theme running through the chapters is access to care, and how it is shaped by moral economies, by what can be said and known, and by political and economic power. Health Care Reform and Globalisation confronts the interpretations and experiences of patients, professionals, and politicians of health care transformation in practice. It will be of interest to scholars from a range of diverse disciplinary backgrounds, including public health, anthropology, area studies, sociology, politics, social policy, geography and economics"--Provided by publisher.
Producing public opinion : how the insurance industry shaped US health care / Wendell Potter -- The break-up of the English NHS : the new market bureaucracy needs information systems based on members and not geographic populations / Allyson Pollock and David Price -- Rethinking problems surrounding access to care : the moral economies shaping health care work forces in Russia and the U.S. / Michele Rivkin-Fish -- Human oriented? : angels and monsters in China's healthcare reform / Mei Zhan -- We are all in this together : European policies and health systems change / Meri Koivusalo -- Catastrophic citizenship and discourses of disguise : aspects of health care change in Poland / Peggy Watson -- The making of health care policy in contemporary hungary / Terry Cox and Sandor Gallai -- Community health services in urban China : a geographical case study of access to care / Yu Wang [and others] -- "Health care and change" : popular protest and building alternative visions of health systems at the end of empire / Howard Waitzkin and Rebeca Jasso-Aguilar.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Health care reform -- United States; Health care reform -- China; Health care reform -- Europe; Medical policy -- United States; Medical policy -- China; Medical policy -- Europe; Electronic books